SMEs CREATIVE ECONOMY IN THE COVID-19 - Sungkawati, Endang (Archives of Business Research, 2021)
Small and Medium Enterprises (SMEs), which experienced a decline due to the COVID-19 pandemic, where MSMEs experienced a decline in terms of capital, marketing, labor, and their assets. MSMEs, which have been said to be productive economic enterprises that are quite strong, are powerless to face the crisis during the Covid 19 pandemic. The government has issued several policies related to decreased income due to the Covid-19 outbreak by providing incentives in the financial sector, namely debt relief for MSME players. The government also encourages MSMEs to innovate and be creative by taking advantage of this geographical advantage into opportunities. In addition, the government also needs to provide a stimulus to maintain people’s purchasing power in the midst of this crisis so that the benefits provided to the economy can be felt.